2019
DOI: 10.1002/cam4.2557
|View full text |Cite
|
Sign up to set email alerts
|

SIRT4 enhances the sensitivity of ER‐positive breast cancer to tamoxifen by inhibiting the IL‐6/STAT3 signal pathway

Abstract: Recent advances in endocrine therapy have improved the prospects for estrogen receptor‐positive breast cancer. Tamoxifen is an effective drug for patients with estrogen receptor‐positive breast cancer, but the development of resistance is common. Therefore, discovering ways to enhance the sensitivity of cancer cells to tamoxifen may help improve breast cancer treatment. We studied the biological role of sirtuin 4 (SIRT4) in tamoxifen‐treated MCF7 and T47D cells. The levels of the MYC proto‐oncogene (MYC) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…A study also demonstrated that SIRT4 is a substrate of ubiquitin-like with plant homeodomain and ring finger domains 1 (UHRF1) and negatively regulated aerobic glycolysis, tumor proliferation, and metastasis of pancreatic cancer cells ( 95 ). A recent study also suggested that SIRT4 overexpression could heighten the sensitivity of ER-positive breast cancer to tamoxifen via inhibiting the interleukin-6/STAT3 pathway ( 102 ).…”
Section: Functions Of Sirt4 In Human Cancermentioning
confidence: 99%
“…A study also demonstrated that SIRT4 is a substrate of ubiquitin-like with plant homeodomain and ring finger domains 1 (UHRF1) and negatively regulated aerobic glycolysis, tumor proliferation, and metastasis of pancreatic cancer cells ( 95 ). A recent study also suggested that SIRT4 overexpression could heighten the sensitivity of ER-positive breast cancer to tamoxifen via inhibiting the interleukin-6/STAT3 pathway ( 102 ).…”
Section: Functions Of Sirt4 In Human Cancermentioning
confidence: 99%
“… 4 Unfortunately, endocrine resistance interferes with the therapeutic effects of Tam, since approximately 30% of women develop local recurrence or distant metastasis despite the initial beneficial response. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, in HRG-overexpressing ER+/HER2-negative cells, specific neutralization of IL-8 bioactivity likewise reduces the ability of HRG overexpression to increase the non-genomic (e.g., MAPK- and PI3K-induced) unliganded transcriptional activity of ERα. The finding that anti-IL-8 treatment reduced but did not completely block the E 2 -independent hyperactivity of ERα in the continuous presence of up-stream oncogenic stimuli such as HRG suggests a need not only for combined treatment with drugs capable of impeding ligand-induced HER2/HER3 signaling (e.g., pertuzumab) but also the potential involvement of additional HRG-driven ERα co-activating cytokines (e.g., IL6, which is known to be repressed by E 2 -driven activation of ERα but drives endocrine therapy resistance by various mechanisms including direct transcriptional activation of ERα [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ]). In this complex scenario of multiple cytokines driving endocrine resistance in HRG-overexpressing ER+ breast cancer cells, the sole blockade of IL-8 bioactivity might become inadequate in the presence of an augmented availability of IL-6 downstream of the HRG-activated HER2/HER2 oncogenic unit.…”
Section: Discussionmentioning
confidence: 99%